Case Report: Subacute thyroiditis after receiving inactivated SARS-CoV-2 vaccine (BBIBP-CorV) - Pi, Linhua; Lin, Jian; Zheng, Ying; Wang, Zhen; Zhou, Zhiguang (Frontiers in Medicine, 2022)
Background: Subacute thyroiditis, an inflammatory disease, has been reported caused by vaccines in rare cases. In the context of coronavirus disease 19 pandemic, various SARS-CoV-2 vaccines have been developed and may be potential triggers for subacute thyroiditis. Case Presentation: We report a case of subacute thyroiditis 3 days after receiving the second dose of inactivated SARS-CoV-2 vaccine (BBIBP-CorV). The patient did not report a previous history of thyroid disease, upper respiratory tract infection, or COVID-19. Physical examination, laboratory testing, ultrasonography, and radioactive iodine uptake were consistent with subacute thyroiditis. During follow-up, the patient recovered from symptoms, signs, and imaging changes except for hypothyroidism requiring an ongoing thyroxine replacement. Conclusions: Inactivated SARS-CoV-2 vaccine may be a causal trigger leading to subacute thyroiditis. Clinicians should be aware of subacute thyroiditis as a possible thyroid related side effect of inactivated SARS-CoV-2 vaccine.